Inmates as Labour Pool: A Case of Inter-organizational Collaboration. (August 2020) - Shree, Sonal; Brahmankar, Yogesh; Singh, Ardhendu Shekhar
Businesses grapple with mounting costs of accessing labour pools for recruitment. At the same time, the jail administrations struggle to find recruiters for a skilled group of convicts. Can collaboration help? It is in this light that the case focusses on the prison system in India and the provision of training and employment within the jail premises. The jail industries serve the dual role of production and training units for convicts and equip them with the necessary skills to help them earn wages as their source of livelihood for the present as well as to secure their future. Inter-organizational collaboration in this case has the potential to provide the much-needed impetus by offering a much larger number of tasks required to engage all convicts. The case highlights the challenges faced by jail authorities in the absence of sufficient tasks versus the increasing number of convicts, and the dilemma and scepticism of businesses in recruiting from prisons. It also leads to the innovative and socially responsible aspect of training and recruitment in organizations through initiatives at the Yerwada and Kolhapur Central jails in Maharashtra, India. Dilemma: Purposive engagement of prisoners outside the prison without any breach of security was a prime concern. An opportunity or risk, what could it turn out to be? Theory: Inter-organizational collaboration Type of the Case: Problem solving, Primary data Protagonist: DIG Sathe Options: The jobs were selected based on the security needs, matching competency, low set-up and training cost and future expansions. Initially jail authorities leased out portions of premises to firms. Inventory were brought in the jail and finished items were transported back to the user. Discussions and Case Questions: How to change the stereotypical portrayal of jail environment as a place to torture inmates in an effort to transform? How can firms be attracted to recruit prison inmates? Which processes will lead to reformation and rehabilitation of inmates? How can the operation be scaled up without posing a threat to security? Which measures will help in diffusing tension within a jail? Whether any inter-organizational collaboration leading to recruitment from prisons would mean an opportunity for corporate or corrective reform for inmates or a morsel of both?